Chemokine-Binding Proteins Encoded by Parapoxvirus of Red Deer of New Zealand Display Evidence of Gene Duplication and Divergence of Ligand Specificity - Sharif, Saeed; Ueda, Norihito; Nakatani, Yoshio; Wise, Lyn M.; Clifton, Sheree; Lateef, Zabeen; Mercer, Andrew A.; Fleming, Stephen B. (Frontiers in Microbiology, 2019)
Parapoxvirus of red deer in New Zealand (PVNZ) is a species of the Parapoxvirus genus that causes pustular dermatitis. We identified a cluster of genes in PVNZ that encode three unique chemokine-binding proteins (CBPs) namely ORF112.0, ORF112.3 and ORF112.6. Chemokines are a large family of molecules that direct cell trafficking to sites of inflammation and through lymphatic organs. The PVNZ-CBPs were analysed by surface plasmon resonance against a broad spectrum of CXC, CC, XC and CX3C chemokines and were found to differ in their specificity and binding affinity. ORF112.0 interacted with chemokines from the CXC, CC and XC classes of chemokines with M affinities. The ORF112.3 showed a preference for CXC chemokines, while ORF112.6 showed M affinity binding for CC chemokines. Structural modelling analysis showed alterations in the chemokine binding sites of the CBPs, although the core structure containing two ß-sheets and three α-helices being conserved with the other parapoxvirus CBPs. Chemotaxis assays using neutrophils and monocytes revealed inhibitory impact of the CBPs on cell migration. Our results suggest that the PVNZ-CBPs are likely to have evolved through a process of gene duplication and divergence, and may have a role in suppressing inflammation and the anti-viral immune response.